Investigation of Weeds in Wheat Crops of Tehsil Kotli, Kotli Azad Jammu and Kashmir, Pakistan - Shah, Syed Awais Hussain (International Journal of Scientific Research in Biological Sciences, 2020)
Weed infestation is one of the most drastic factors which adversely affects the grain quantity as well as quality in cereal crops like wheat, which is a worldwide cultivated staple food crop. The aim of this research was to survey the weed species found in wheat growing in tehsil Kotli. The survey was performed from seeding to harvest during the wheat campaign 2019-2020. Thirty one weed species belonging to twenty six genera and sixteen families were reported. Most weed species (26%) belonged to the Asteraceae family followed by Poaceae (13%), Brassicaceae (10%), Polygonaceae (10%) and Papaveraceae (6%). Other minor families found belonged to Amaranthaceae, Apiaceae, Caryophyllaceae, Cyperaceae, Euphorbiaceae, Lamiaceae, Malvaceae, Oxalidaceae, Primulaceae, Ranunculaceae and Saxifragaceae. Rumex genus was the most represented by four species followed by Cirsium, Fumaria and Lepidium. Controls of these weeds require awareness of farmers about the use of ecofriendly methods (i.e. physical, biological and crop rotation) in a weed integrated management.